Intercorporeality: emerging socialities in interaction - Meyer, Christian; Streeck, Jürgen; Jordan, J. Scott; Streeck, Jürgen (Oxford University Press, 2017)
Drawing together theory and advanced empirical research from a variety of disciplines, this book offers a new multidisciplinary perspective on human interaction. It conceives of the living body in terms of its interaction with other bodies, and its openness to and engagement with the material and cultural world.
Previously issued in print: 2017. - Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on July 18, 2017)